1998
DOI: 10.1890/0012-9658(1998)079[0065:ronrop]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Northern Red Oak: Positive and Negative Effects of Competitor Removal

Abstract: The decreased ability of northern red oak (Quercus rubra) to regenerate throughout its range in the eastern United States has important ecological and economic implications. We studied regeneration of northern red oak in oak and pine stands on moderately productive sites in northern Lower Michigan. Our objectives were (1) to investigate the hypothesis that regeneration of northern red oak is more successful in pine than in oak stands and (2) to test whether removal of potential overstory and understory competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(46 citation statements)
references
References 23 publications
1
43
0
2
Order By: Relevance
“…However, field studies of competition can be complicated by the presence of herbivores within the system (Reader, 1992;Hulme, 1996;Reader and Bonser, 1998). By altering the competitive environment, researchers may also alter the amount of herbivory experienced by a plant (Reader, 1992;Burger and Louda, 1995;Buckley, Sharik, and Isebrands, 1998). Because of these potential field complications, greenhouse studies may be the only way to effectively determine the individual and combined effects of herbivory and competition on plant recruitment and growth where herbivore removal is not practicable.…”
mentioning
confidence: 99%
“…However, field studies of competition can be complicated by the presence of herbivores within the system (Reader, 1992;Hulme, 1996;Reader and Bonser, 1998). By altering the competitive environment, researchers may also alter the amount of herbivory experienced by a plant (Reader, 1992;Burger and Louda, 1995;Buckley, Sharik, and Isebrands, 1998). Because of these potential field complications, greenhouse studies may be the only way to effectively determine the individual and combined effects of herbivory and competition on plant recruitment and growth where herbivore removal is not practicable.…”
mentioning
confidence: 99%
“…Lorimer et al [35] observed that the density of the intermediate layer of vegetation negatively affected the growth and survival of oak seedlings, while understory vegetation competition had no effect. Others found similar results, namely the predominant effect of competition produced by the overstory canopy on that of the lower vegetation layer [1,11,15,48]. Grassi and Giannini [19] found strong growth and morphological relations with available light (canopy induced), but none with competing sapling's density.…”
Section: Competition Stratificationmentioning
confidence: 77%
“…Three studies have reported that decreased stand density, which would have the effect of making planted trees more visible, resulted in greater deer herbivory [11,18,51]. For two of these studies, however, that of Gordon et al [18] and of Truax et al [51], the determining factor was the understory vegetation, more than the overall openness of the stand.…”
Section: Herbivorymentioning
confidence: 99%
See 1 more Smart Citation
“…Importanti diven gono in questa fase anche i fenomeni di competizio ne intraspecifica fra cespuglio e semenzale per luce, acqua e nutrienti che, secondo alcuni autori, si tradu cono in un minore accrescimento delle specie arbo ree (Buckley et al 1998, Rousset & Lepart 2000.…”
Section: Facilitazione Dei Cespugliunclassified